Przesłanki i sposoby wspierania małej i średniej przedsiębiorczości w Polsce - wybrane aspekty - Potoczna, Iwona (Circumstances and ways of supporting of small and medium entrepreneurship - the chosen aspects, 2006)
Supporting small and medium entrepreneurship is an important element of economics policy programmes in many well-developed countries. In times when socialist doctrine was functioning, this kind of activity was openly fought against. Entrepreneurship was very often discriminated and rationed. For this reason, the problem is of great importance nowadays. These companies constantly enlarge their share in the Gross Domestic Product, in employment and export. Mainly these enterprises create new workplaces. This sector is the main employer and that is why one should make appropriate conditions for growth and development, because it is the way of limiting the growing unemployment and creating new workplaces. The goal of this article is to discuss the circumstances of supporting of small and medium entrepreneurship and the growth of importance in the Polish economy, as well as to comment on the aims of government policy toward the group of such entrepreneurs and ways of supporting their growth.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 188-194